Pengalaman Malaysia terhadap pendekatan kuasa dalam proses rundingan Protokol Montreal ke arah pembangunan mapan - Muhammad Rizal Razman; Abdul Samad Hadi; Jamaluddin Md. Jahi; Abdul Hadi Harman Shah (Environmental Management Society, Malaysia, 2010)
Malaysia has been recognised by the international community as one of dedicated countries in conservation of global environment, which include issues on depleting global ozone layer. Meanwhile, Montreal Protocol is one of the successful international environmental law. Montreal Protocol managed to seek international environmental cooperation among almost all of the states in the world. All of these states have already agreed to ratify the Montreal Protocol. The Montreal Protocol has been enacted for the protection of the ozone layer by taking precautionary measures to control world emissions of substances that deplete the ozone layer. Some of the international environmental law scholars suggested that power approach might influence in the negotiations of creating international environmental law. Moreover the existence of the superiority power in economy, military, technology and science would lead for hegemony. This hegemony most likely would build up more cooperation among states and subsequently influence in the negotiations of creating MEAs, which include the Montreal Protocol. Therefore, the primary purpose of this study is to explain the influence of power approach in the international environmental law on regards of the Montreal Protocol’s negotiations and the relations of the interstates participation response focusing on Malaysia’s experinces. Meanwhile, this study uses a qualitative approach, which is based on interviews among Malaysian representatives in the negotiation processes of the Montreal Protocol. Finally, the results potentially provide with better understanding of the influence of power approach in the international environmental law